Effects of Pre-freezing and Vacuum Freeze-drying on Physicochemical Properties and Gelling Characteristics of Myofibrillar Protein from Nemipterus virgatus - Qiuyan SHI; Duanquan LIN; Wenxiong HE; Kang LIU; Lingjing ZHANG; Ling WENG; Lechang SUN (Shipin gongye ke-ji)
To investigate the effects of vacuum freeze-drying on the properties of frozen surimi powder, myofibrillar protein (MP) from Nemipterus virgatus was taken as the research object. The changes of physicochemical properties of MP during the processes of pre-freezing and vacuum freeze-drying, and the effect of transglutaminase (TGase) on the gelling characteristics of MP were investigated. The results showed that compared with the untreated group, the turbidity and particle size of MP treated by pre-freezing and vacuum freeze-drying increased significantly (P<0.05) with the decreased solubility by 32.3% and 42.0%, indicating that proteins aggregation occurred during the processing. The decreased total sulfhydryl content by 27.3% and 45.35%, and the increased carbonyl content by 112.2% and 181.5%, respectively, showing that oxidative denaturation occurred. The content of α-helix structure decreased and the maximum endogenous fluorescence intensity of MP treated by pre-freezing and vacuum freeze-drying decreased from 5879 to 5487 and 4144, respectively, revealing that the ordered structure of protein was destroyed and the microenvironment was changed. The gels prepared by the untreated group had the highest storage modulus G′ value, followed by the pre-freezing treatment group and then the vacuum freeze-drying group. The addition of TGase could improve the rheological properties of MP. The gel network structure of MP was clearly visible in the untreated group, and the uneven network structure appeared in the pre-freezing group, while the vacuum freeze-drying group could not form gel network structure. The addition of TGase promoted the formation of denser and more uniform gel network structure of MP. In summary, the pre-freezing stage and the drying stage in the vacuum freeze-drying could affect the physicochemical properties and gelling characteristics of MP, in which the freezing denaturation of MP caused by the pre-freezing treatment had a significant impact on the aggregation and oxidation of MP, while the dehydration denaturation of MP during the drying phase had a more pronounced effect on the structure of MP. Furthermore, the addition of TGase could improve the gelling characteristics of MP after the pre-freezing and vacuum freeze-drying treatments.